Safe Surgery Checklist, Patient Safety, Teamwork, and Responsibility-Coequal Demands? A Focus Group Study - Elin Thove Willassen; Inger Lise Smith Jacobsen; Sidsel Tveiten (SAGE Publishing, 2018)
The use of World Health Organization's (WHO's) Safe Surgery checklist is an established practice worldwide and contributes toward ensuring patient safety and collaborative teamwork. The aim of this study was to elucidate operating room nurses' and operating room nursing students' experiences and opinions about execution of and compliance with checklists. We chose a qualitative design with semistructured focus group discussions. Qualitative content analysis was conducted. Two main themes were identified; the Safe Surgery checklists have varied influence on teamwork and patient safety, and taking responsibility for executing the checks on the Safe Surgery checklist entails practical and ethical challenges. The experiences and opinions of operating room nurses and their students revealed differences of practices and attitudes toward checklist compliance and the intentions of checklist procedures. These differences are related to cultural and professional distances between team members and their understanding of the Safe Surgery checklists as a tool for patient safety.